Creepy creatures - Keenan, Sheila; Stine, R. L. (New York : Graphix, 2006)
Comic artists Gabriel Hernandez, Greg Ruth, and Scott Morse adapt and illustrate three R. L. Stine stories, in which a girl pays a frightening visit to her grandparents' farm, a boy meets a stray dog that just might be a werewolf, and a brother and sister encounter a snow monster in Alaska--and in California.
The werewolf of Fever Swamp / adapted and illustrated by Gabriel Hernandez -- The scarecrow walks at midnight / adapted and illustrated by Greg Ruth -- The abominable snowman of Pasadena / adapted and illustrated by Scott Morse.
"R.L. Stine, Goosebumps.".
Booklist.
School Library Journal.
Wilson's Junior High School.
6.1
5-8
Keywords: Cartoons and comics; Monsters -- Fiction; Comic books, strips, etc; Monsters -- Fiction; Graphic novels